Andrea Handley in conversation with Jerome Carson. Issue 3 (16th May 2020) - Handley, Andrea; Carson, Jerome
Abstract : Purpose: The purpose of this paper is to provide a profile of Andrea Handley. Design/methodology/approach: In this case study, Andrea gives a short account of her background and is then interviewed by Jerome. Findings: Andrea outlines a number of issues from her childhood that led to her later mental health problems. Research limitations/implications: Individual case studies are of course just the story of one person's difficulties. For too long in psychiatry, case studies were written by professionals about their lives and problems. First person accounts allow the individual to tell their own narrative. Practical implications: Andrea is not the first person to talk about the delay in access to mental health services. As she notes, 16 years on, she is still waiting for that referral! She notes that a friend of her could not wait even the three months that she had been and tragically took her own life. Social implications: So much of Andrea's story is overshadowed by loss, especially the death of her brother when she was a teenager. As a society, we are no as well "prepared" for death, as older generations. The coronavirus pandemic is bringing our mortality home to all of us. Originality/value: Patricia Deegan once asked, "How much loss could a human heart hold?" In this moving account Andrea lets us see the huge losses she has sustained and yet she is still determined to try and help others who are suffering. Hers is truly a remarkable life.